ALGEBRA 1

posted by .

Solve by whatever Method
1. X^2 +8X = -16
X^2 +8X +16 = -16 +16
(X +4)^2 =0
X+4 =+/- SQRT 0
X=-4+/- 0
X=-4, X=4

2. 3x^2-2x-5=0
X=-b+/- sqrt (b)^2-4ac
2a a=3 ,b=-4,c=-5
X=-(-2)+/- Sqrt (-2)^2-4(3)(-5)
2(3)
X=2+/sqrt64 = 2+/-8
6
X= 2+8=10/6=1 2/3, x=2-8=-6/6=-1
Solution set is 1 2/3, -1

Solve by completing the square
3. X^2-x-1=0
X^2-x=1
X^2-1/2x=1/2
X^2-1/2x+ (1/2)^2=1/2 +(1/2)^2
X^2x+1/4=1/2+1/4
(X-1/4)^2=1/2
X-1/4=+/1/2
x=1/2+/-1/2
x=1, x=0

Just want to see if I am on the right path. Thanks Much!!!








#1, OL
#3, look at lines 5 and 6
1/2 + 1/4 = 3/4 not 1/2, take it from there

in #2 you are guilty of "bad form"
you have X= 2+8=10/6=1 2/3, x=2-8=-6/6=-1

using the = sign means that whatever you just wrote is equal to the next part.

I see x = 2+8 = 10/6..

2+8 is not equal to 10/6, you can't just drop numbers and then bring them back
that line should have read:
x=(2+8)/6 or x =(2-8)/6
x=10/6 or x=-6/1
x=5/3 or x = -1

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Inequality

    When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution?
  2. Math(Roots)

    sqrt(24) *I don't really get this stuff.Can somebody please help me?
  3. math

    solve 2x^2+3x+8=0 and express the solutions in a+bi form. Let's use the quadratic formula to solve for x and express those solutions in a+bi form. x = [-b + or - sqrt(b^2 - 4ac)]/2a Note: sqrt = square root. a = 2, b = 3, and c = 8 …
  4. math,algebra,help

    Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
  5. Mathematics

    sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So you can see the steps — sqrt 6 * sqrt 8 = sqrt 48 sqrt 7 * sqrt 5 = sqrt 35 I hope this helps a little more. Thanks for asking.
  6. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
  7. Calculus - Second Order Differential Equations

    Posted by COFFEE on Monday, July 9, 2007 at 9:10pm. download mp3 free instrumental remix Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 …
  8. Calculus

    Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 …
  9. Math/Calculus

    Solve the initial-value problem. Am I using the wrong value for beta here, 2sqrt(2) or am I making a mistake somewhere else?
  10. Algebra

    Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?

More Similar Questions